Territorialidad, guerra y encomienda. Los pulares entre 1552 y 1633 (Gobernación del Tucumán, Virreinato del Perú) - Miguel Nicolás Hopkins Cardozo (Nuevo mundo - Mundos Nuevos, 2021)
With the name of pulares an indigenous group is known that the historiography mostly places in the north of the Calchaquí valley until its reduction in the Lerma valley, describing it as a “multi-ethnic group” that, as a continuation of its alliance with the Incas, establishes a colonial pact with the Spaniards. This paper proposes a review of the interaction between Pulares and Spaniards, starting from the concept of interdigitation proposed by José Luis Martínez to analyze the mobility of the Atacameños. Although the colonial agents, and, later, certain academic works, have tried to anchored them to a reduced environment, the Pular have maintained links with different indigenous groups from areas of the puna, valleys and ravines. It is proposed in this work that this allowed them, according to the context, to join the rebels or ally themselves with the Spaniards.